The Civil War as Photographed by Mathew Brady. The Constitution Community Civil War and Reconstruction (1850-1870) - Perry, Douglas; National Archives and Records Administration, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2001)
Many historians call the Civil War the central event in U.S. history. The formation of the U.S. Constitution corrected the autonomy of individual states that the Articles of Confederation did not harness. The young country struggled for 75 years to find a graceful balance between the power of the federal government and that of the states. The states rights and the slavery issue propelled the country into civil war. Mathew Brady and his colleagues used a new medium, photography, to document battlefields, camps, towns, and people touched by the War. No battles were photographed because the still primitive technology of photography required that subjects be still at the moment the camera's shutter snapped. This lesson examines how the Civil War threatened the very purpose of the U.S. Constitution as stated in the Preamble. The lesson correlates to the National History Standards and to the National Standards for Civics and Government. It uses 16 Mathew Brady photographs taken during the Civil War as the primary sources. The lesson provides historical background on the sociology of the Civil War, photography, and lists four resources. It offers instruction for implementing six diverse teaching activities, such as document analysis, a reading assignment and discussion, a writing assignment, research on other Civil War photographs, and an extension activity. (Contains a photograph analysis worksheet.) (BT)
Availability: National Archives and Records Administration, 700 Pennsylvania Avenue, N.W., Washington, DC 20408. Tel: 866-325-7208 (Toll Free); e-mail: inquire@nara.gov. For full text: http://www.nara.gov/education/cc/main.html.
ERIC Note: For related lesson plans, see ED 461 604-607 and ED 461 609-615. Photographic images may not reproduce clearly.
Practitioners.
Teachers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Civil War (United States); Government Role; Photographs; Photography; Primary Sources; Secondary Education; Slavery; Social Studies; United States Constitution; Articles of Confederation -- Brady (Mathew) -- National Civics and Government Standards -- National History Standards; Guides, Classroom -- Teacher